Side effects of monaural beat stimulation during sustained mental work on mind wandering and performance measures - Schmidt, Lucy Marlene; Chaieb, Leila; Derner, Marlene; Reber, Thomas P.; Fell, Juergen (Frontiers in Psychology, 2024)
Excessive mind wandering (MW) contributes to the development and maintenance of psychiatric disorders. Previous studies have suggested that auditory beat stimulation may represent a method enabling a reduction of MW. However, little is known about how different auditory stimulation conditions are subjectively perceived and whether this perception is in turn related to changes in subjective states, behavioral measures of attention and MW. In the present study, we therefore investigated MW under auditory beat stimulation and control conditions using experience sampling during a sustained attention to response task (SART). The subjective perception of the stimulation conditions, as well as changes in anxiety, stress and negative mood after versus before stimulation were assessed via visual-analog scales. Results showed that any auditory stimulation applied during the SART was perceived as more distracting, disturbing, uncomfortable and tiring than silence and was related to more pronounced increases of stress and negative mood. Importantly, the perception of the auditory conditions as disturbing was directly correlated with MW propensity. Additionally, distracting, disturbing and uncomfortable perceptions predicted negative mood. In turn, negative mood was inversely correlated with response accuracy for target stimuli, a behavioral indicator of MW. In summary, our data show that MW and attentional performance are affected by the adverse perception of auditory stimulation, and that this influence may be mediated by changes in mood.